The effectiveness of tour guide’s interpretation in creating mindful tourists: A study on the Penang world heritage sites - Mohamed Rosli, Nor Ez-Zatul Hanani; Mohamed, Ramli; Md Noor, Shuhaida; Khor , Yoke Lim (2013)
The number of tourists to heritage sites has increased tremendously in recent years and has contributed to the growth of the nation’s economy since heritage tourism has become the central focus of Malaysia’s attraction to outsiders especially after the declaration of Malacca and Penang as world heritage sites by UNESCO in 2008. When planned and managed effectively heritage tourism can realize positive impacts but when poorly managed heritage tourism can be devastating and causing damage to resources from inappropriate treatments and uncontrolled visitation. Therefore, this study intends to analyse how can effective interpretation provide by tour guide can create mindful tourists which is tourist who has greater learning, high satisfaction and more understanding in order to give positive impact to the heritage tourism. With the greater learning experience and knowledge gain by the tourist from the interpretation by the tour guide, they are able to understand the place more and tend to appreciate the place better as they are able to distinguish their actions that may have impact at the heritage sites hence the heritage can be conserved.